ANALISIS POLA SIRKULASI BANDAR UDARA INTERNASIONAL AHMAD YANI SEMARANG - Evo Elvaro Readyson; Ratri Septina Saraswati (Program Studi Arsitektur, Fakultas Teknik dan Informatika, Universitas PGRI Semarang, 2022)
ABSTRACTAir transportation is one part of the transportation sector that has shown very rapid development. Progress in the transportation sector has changed the image and pattern of economic development, population mobility, and national development. To overcome this, a plan is needed to increase its needs to support today's and future activities, this needs to be done. Airport development planning is required to have a large capacity, so that it requires planning of air traffic activities and to calculate the increasing number of passengers in the long run, public transportation that requires development funds and limited space for development areas. With this limitation, the quality of service for transportation must be improved. To increase the number of passengers, aircraft is needed and the need to increase the number of passengers. Some things that became the discussion at Semarang Ahmad Yani International Airport are: (1) increasing passenger capacity, (2) Improving Space Needs, (3) increasing circulation and (4) making this airport suitable for use as a venue for Hajj embarkation. The points above are then analyzed to become material or a reference for the future. Keywords: Air Transportation, Space Needs, Space Circulation